PENGARUH TERAPI ORAL MOTOR DENGAN GANGGUAN REFLEK HISAP LEMAH PADA BAYI PREMATUR - Widianti, Sherly; Fauziah, Neneng (Jurnal Kesehatan dan Pembangunan, 2025)
According to WHO data (2022), in 2020, nearly half (47%) of all under-five deaths occurred during the neonatal period (the first 28 days of life). One of the causes of neonatal death is premature birth. In premature infants, the sucking and swallowing reflexes are not yet fully developed. One of the treatments to improve the sucking reflex in infants is oral motor therapy. The purpose of this study was to determine the effect of oral motor therapy on weak sucking reflex disorders in premature infants in the NICU of Siti Fatimah Regional Hospital in 2025. This research used a pre-experimental design with a one-group pretest-posttest approach. The population of this study consisted of all premature infants in the NICU of Siti Fatimah Regional Hospital, South Sumatra Province, from December 30, 2024, to January 30, 2025. The sample consisted of 15 respondents selected through purposive sampling. Statistical analysis was performed using the paired sample t-test. The results showed that oral motor therapy had a significant effect on weak sucking reflex disorders in premature infants in the NICU of Siti Fatimah Regional Hospital in 2025, with a p-value of 0.000. It is recommended that better nursing care be provided, especially for premature infants, through collaboration with pediatricians to improve weak sucking reflexes in premature infants using oral motor therapy.